Recent foreign investment in Peru and competitive development - Vera-Vassallo, Alejandro (Universidad del Pacífico, 1996)
The article analyses recent foreign investment in Peru under the new development strategy. It examines the changes that have come about in the composition of flows, the new features they present, the explanatory factors and the significance of all of these from the standpoint of the aimed competitive development.   The article concludes that there is a need to combine an explicit development strategy with a regulatory framework and adequate macroeconomic management, in a way oriented towards expanding Peru's stock of technological know-how. Such a policy should include an institutional development oriented towards increasing "social technological absorption capacity", so that the contribution of transnational corporations and foreign investment will give rise to a process of industrial and technological learning as a prelude to following phases of competitive innovation and consequent dynamic integration into the global economy.